I-VIDEO IN BASIC PHOTOGRAPHY COURSE FOR SPECIAL EDUCATION NEEDS (Proceedings of International Conference on Special Education, 2015)
The Ministry of Education in Malaysia believes that everyone deserves a chance in education. Because of this belief, the Department of Community College Education has launched various programs for special needs students. Paya Besar Community College (KKPB) had been chosen among others to run a Certificate in Basic Photography (KFI) program starting from July 2013. The special needs students that are expected to enroll in this course are students with learning disabilities. Learning disabilities are neurologically-based processing problems that can interfere with learning basic skills. These conditions must be clinically diagnosed and validated by medical experts. Most of PBCC special needs students have problems focusing, remembering and processing information. These students also have trouble associating their existing knowledge with new knowledge as well as applying it in their learning environment. The I-video is design to assist in the learning and teaching process for this program. The I-video was developed using the Adobe Premiere Pro CS4 with the combination of the blue screen effect technology and suing a studio concept. This innovation applies multimedia interactions that can appeal to special needs students thus completing the learning and teaching proses. The outcome of the I-video has shown an increase in the learning and teaching proses. The concept of this I-video has high potential to be used throughout the Education institution in Malaysia.